Blue future : protecting water for people and the planet forever - Barlow, Maude (New Press, The, 2013)
"In her bestselling books Blue Gold and Blue Covenant, world-renowned water activist Maude Barlow exposed the battle for ownership of our dwindling water supply and the emergence of an international, grassroots-led movement to reclaim water as a public good. Since then, the United Nations has recognized access to water as a basic human right-but there is still much work to be done to stem this growing crisis. In this major new book, Barlow draws on her extensive experience and insight to lay out a set of key principles that show the way forward to what she calls a "water-secure and water-just world." Not only does she reveal the powerful players even now impeding the recognition of the human right to water, she argues that water must not become a commodity to be bought and sold on the open market. Focusing on solutions, she includes stories of struggle and resistance from marginalized communities, as well as government policies that work for both people and the planet. At a time when climate change has moved to the top of the national agenda and when the stage is being set for unprecedented drought, mass starvation, and the migration of millions of refugees in search of water, Blue Future is an urgent call to preserve our most valuable resource for generations to come. "--